Obstetrics and gynecology clerkship directors' experiences advising residency applicantsAJOG Global Reports at a Glance - Helen K. Morgan, MD; Laura Baecher-Lind, MD, MPH; Rashmi Bhargava, MD; Susan Cox, MD; Elise Everett, MD; Angela Fleming, DO; Scott Graziano, MD, MS; Chris Morosky, MD, MS; Celeste Royce, MD; Tammy Sonn, MD; Jill Sutton, MD; Shireen Madani Sims, MD (Elsevier, 2023)
BACKGROUND: The evolving landscape of application processes for obstetrics and gynecology residency applicants poses many challenges for applicants and advisors. The lack of data coordination among national groups creates crucial gaps in information for stakeholder groups. OBJECTIVE: This study aimed to identify the current state of the advising milieu for obstetrics and gynecology residency applicants and their career advisors, the annual Association of Professors of Gynecology and Obstetrics survey focused on US clerkship directors' experiences advising students through these processes. STUDY DESIGN: A 23-item anonymous survey was developed that asked respondents about demographics and outcomes for the students that they advised through the 2021 application process and their experiences with dual applicants and students not matching. The survey was sent electronically to all obstetrics and gynecology clerkship directors with active Association of Professors of Gynecology and Obstetrics memberships in April 2021. RESULTS: Of 224 total clerkship directors, 143 (63.8%) responded to the survey, Of the 143 respondents, almost all (136 [95.1%]) served as career advisors, and 50 (35.0%) were aware of students dual applying. Furthermore, obstetrics and gynecology was rarely the backup to a more competitive specialty. For the 2021 application cycle, 79 of 143 respondents (55.2%) reported having students not successfully match into obstetrics and gynecology, with "academic concerns" followed by "poor communication skills" as the primary reasons cited for students not matching. CONCLUSION: This snapshot of clerkship directors' experiences advising students in the residency application process reveals notably high rates of dual applicants and students not matching into obstetrics and gynecology. This work fills key gaps in our knowledge of current processes and highlights the importance of career advising at multiple points during the application process.